Strategi Perancangan Struktur Organisasi Formal melalui Tahapan Mekanisme dan Implementasinya (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Formal organizational structures are crucial for ensuring the effectiveness, efficiency, and accountability of work processes within an institution. However, many organizations still face challenges such as overlapping tasks, ineffective communication, and inadequate control mechanisms. This study aims to analyze formal organizational structure design strategies through systematic steps, implementation mechanisms, and ongoing evaluation. The research method used is a literature review, based on a review of the latest scientific sources (books, journals, and research reports) related to organizational theory and structural design. The results indicate that organizational structure design should begin with defining objectives, analyzing activities, departmentalizing, establishing hierarchical relationships, coordinating mechanisms, and evaluating. Implementation mechanisms include socialization, human resource capacity development, process integration with technology, monitoring, and change management. The literature review also confirms that alignment between strategy, structure, and business processes is a key factor in improving organizational performance. Therefore, organizational structures must be adaptive, responsive, and data-driven to face the challenges of an ever-evolving strategic environment.